2020
DOI: 10.1016/j.rmed.2020.106116
|View full text |Cite
|
Sign up to set email alerts
|

Changes in and predictors of pain and mortality in patients with chronic obstructive pulmonary disease

Abstract: This longitudinal study of patients with chronic obstructive pulmonary disease (COPD) aimed to investigate changes in pain characteristics (i.e., occurrence, intensity, and interference) and covariates associated with pain from study enrollment to 12 months, and to investigate if the different pain characteristics were associated with 5-year mortality. In total, 267 patients with COPD completed questionnaires five times over 1 year. The mean age of the patients was 63 years (standard deviation: 9.0), 53% were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 77 publications
(124 reference statements)
1
2
0
Order By: Relevance
“…This finding is consistent with previous research that confirms a stable prevalence of pain in patients with COPD over time [49]. Pain has been associated with several symptoms, comorbidities, depression, as well as increased mortality within 5 years in COPD patients [50]. Research also shows that chronic pain is common in patients with COPD and that it has a negative impact on mood, breathlessness, interference with daily activities, and quality of life, and should be included in the management of the disease [51].…”
Section: Discussionsupporting
confidence: 92%
“…This finding is consistent with previous research that confirms a stable prevalence of pain in patients with COPD over time [49]. Pain has been associated with several symptoms, comorbidities, depression, as well as increased mortality within 5 years in COPD patients [50]. Research also shows that chronic pain is common in patients with COPD and that it has a negative impact on mood, breathlessness, interference with daily activities, and quality of life, and should be included in the management of the disease [51].…”
Section: Discussionsupporting
confidence: 92%
“…De Miguel-Díez et al recently found that among people with COPD, 40% reported CNP [35]. Similarly, in a COPD population, Bentsen et al reported a high prevalence of NP [36]. As in asthma patients, hyperventilation has been shown to affect the respiratory muscles, causing alterations in the neck, shoulders, and thoracic region.…”
Section: Discussionmentioning
confidence: 97%
“…Nurses can retrospectively analyze the predictors of adverse events such as readmission and acute exacerbation in patients with COPD through nursing research, provide early interventions for patients who are likely to experience adverse events, contributing to the primary prevention of COPD-related adverse events. 55,56 Therefore, The hotspot of COPD nursing research has shifted from "rehabilitation" in the period of rapid growth to "predictors" in the period of stable growth, highlighting a shift in the focus of COPD nursing research from tertiary prevention to primary and secondary prevention.…”
Section: Research Hotspotsmentioning
confidence: 99%